Pengaruh Kegiatan Bermain Adonan Sabun terhadap Perkembangan Kreativitas Anak di Raudhatul Athfal 03 Ishlahul Ummah Kota Sawahlunto - Bunga Tri Rahayu; Yulsyofriend (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2019)
Besed on research observations at Raudhatul Athfal 03 Ishlahul Ummah, Kota Sawahlunto, researchers found that the problem of children’s creativity is not optimally developed. This can be seen in the activities of creativity development: coloring pictures, where the average coloring results of children are almost the same as those in LKS. Likewise in the development of other creativity, to make as children like with plasticine, children are only able to imitate other friends to other friends in the example where there is a teacher’s direction. This is due in part to the lack of children’s creativity in creating new works in Raudhatul Athfal 03 Ishlahul Ummah, Kota Sawahlunto. To overcome these problems, researchers look for alter native solutions through the activities of playing soap dough. Therefore through the play of soap dough is thought to influence the development of creativity of children 5-6 years. The purpose of this study was to determine whether the influence of soap dough play activities on the development of creativity of children 5-6 years at Raudhatul athfal 03 Ishlahul Ummah, Kota Sawahlunto. This research uses a quantitative approach with Quasi Experimental design using experimental methods. The study population was all children in Raudhatul Athfal 03 Ishlahul Ummah, Kota Sawahlunto,with the sampling technique being purposive sampling, namely B2 group for the experimental class and B1 group for the control class, each totaling 13 children. Based on data analysis, th experimental group’s average testresults were 62.82 and SD was 7.75 while the control group was 57.69 and SD was 6.08. In testing the hypothesis obtained t count of 2,78595 < and t table of 2.06390 at the real level α = 0.05 (5%) and dk=24. So it can be concluded that the activity of playing soap dough on the development of creativity of children 5-6 years at Raudhatul Athfal 03 Ishlahul Ummah, Kota Sawahlunto 2019/2020 school year.